Forest Sustainability in North Lebanon: A Challenging Complexity in a Changing Environment - Rita El-Hajj; Dalia Al-Jawhary; Tala Moukaddem; Carla Khater (International Journal of Forestry Research)
Forests sustainability is a challenging task in a complex socioeconomic context. North Lebanon is a critical zone harboring forests of key ecological value and is one of the most deprived regions in Lebanon with high poverty rates, where forests are heavily impacted by unsustainable anthropogenic practices. In the global frame of climate change scenarios, this paper tests a multistakeholder, multidisciplinary approach for forest management, combining a joint participatory methodology with stakeholders along with field ecological surveys in the upper Akkar watershed (north Lebanon). A set of participatory tools including stakeholder’s analysis, problem tree, objective tree, and scenario building are tailored to reach this goal. Results exhibit that forest management is not only related to forests per se but also very much linked to the surrounding socioeconomic situation. Involving not only strict silviculture interventions but also a definite consideration of community needs and local economy, the adoption of a multitool, multidisciplinary, multistakeholder approach combines all possible aspects of a challenging context and unfolds complementary processes which all feed back into one target. Yet, it is a time-consuming process, which can easily drown financial and temporal resources and which can sometimes raise unrealistic expectations that are difficult to meet.